MEMAKNAI HAK AKUNTABILITAS DARI DIMENSI KEWAJIBAN DANA PIODALAN - Sriwinarti, Ni Ketut; Sokarina, Ayudia (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
Piodalan is a traditional ceremony of Balinese Hindus. Piodalan is an immaterial religious activity, as a form of belief to Ida Sang Hyang Widhi as the owner of the universe. For the continuity of piodalan, a material value is needed in the form of funds obtained from the contributions of Balinese Hindu society in banjar. The management of these funds is carried out by one of the banjar administrators as treasurer. Accountability for the management of piodalan funds is very unique with cultural of the Hindu-Balinese, and it’s very interesting to study. This study aims to explore the meaning of accountability of piodalan funds for Hindu-Balinese who live in West Lombok. The tools used to analyze the data, the researcher uses a spiritualist interpretive paradigm and a spiritualist phenomenological. The results show the accountability of piodalan funds means the realization of the responsibility or obligation of Hindus to God for the worldly pleasures that given by Almighty which includes five dimensions, namely: clarity, openness, submission, lascarya (sincerity), and manah Kayun (piety).